Ensuring Security and Privacy in Healthcare Systems: A Review Exploring Challenges, Solutions, Future Trends, and the Practical Applications of Artificial Intelligence - Bala, Indu; Pindoo, Irfan; Mijwil, Maad M.; Abotaleb, Mostafa; Yundong, Wang (Jordan Medical Journal, 2024)
Background and Aims: The healthcare system's complex structure presents unique challenges in ensuring security and privacy. This review aimed to explore these challenges in the context of the growing integration of artificial intelligence (AI) in healthcare operations. Materials and Methods: We conducted an in-depth analysis of the healthcare system's architecture, emphasizing the necessity of understanding its multifaceted nature to effectively safeguard sensitive data. We then assessed potential risks and vulnerabilities by reviewing previous cyber-attacks targeting healthcare institutions, establishing a basis for proposing robust countermeasures. Results: The results highlighted the critical importance of protecting healthcare data and details the nature of threats faced by the system. Through examining past incidents, we identified common vulnerabilities and the methods by which they were exploited. Based on these insights, we propose novel strategies aimed at mitigating the impact of these security breaches in the context of healthcare. Conclusions: The integration of AI in healthcare poses both opportunities and challenges for security and privacy. This review addressed the obstacles faced by researchers in ensuring that AI applications in healthcare are secure and respect patient privacy. We emphasized the need for continuous adaptation and improvement to keep pace with evolving threats. Ensuring the security and privacy of healthcare systems in the AI era is essential. This review identified the complexities involved to ensure security and privacy of healthcare systems and outlined proactive strategies to enhance the resilience of healthcare institutions against cyber threats. Continuous research is essential to stay ahead of potential security challenges.